The Translation of English Modals in the Novel Entitled Deck The Halls - Riyanti, Suci (English Journal Antartika, 2023)
This study analyzes the translation of English modals into Indonesian within the context of the novel "Deck the Halls" by Mary Higgins Clark and Carol Higgins Clark. Modals, such as "can," "could," "may," "might," "should," "would," and "must," are crucial in expressing nuances of possibility, necessity, permission, and ability. Their accurate translation is vital for preserving the narrative's tone, intent, and subtlety. This study examines how these English modals are rendered in Indonesian, highlighting translation strategies employed to convey the original meaning effectively. The analysis reveals that modals are often translated through literal and contextual approaches. For instance, "must" is translated as "harus" to convey strong necessity, while "might" is rendered as "mungkin" to express uncertainty. The study also explores challenges such as nuance loss and context sensitivity, which arise due to structural and cultural differences between English and Indonesian. The effectiveness of the translation is evaluated based on how well it retains the original modals' meanings and narrative functions. Overall, this analysis demonstrates that while translating English modals involves navigating complex linguistic and cultural factors, the strategies employed in "Deck the Halls" generally succeed in preserving the narrative's intended tone and meaning.